Family-Based Character Education: The Role of Parenting as the Basic of Character Education for Elementary Children - Prio Utomo; Intan Alawiyah (Journal of Primary Education (JPE), 2022)
One aspect of a child's character development is influenced by parenting, good parenting will certainly support the child's character and vice versa. The purpose of this study is to represent the urgency of parenting as the basis for character education for elementary children. This research method uses field studies. The subjects of the study were Rendra Bimantara's family and Teten Marlena's family in Bumi Ayu Village, Bengkulu City. The results showed that (1) the parenting style used by families in teaching character education to their children uses authoritative parenting; (2) character values instilled in children include religion, honesty, care/empathy, independence, discipline, responsibility, hard work, humility, courage, fairness, patience, tolerance, leadership; (3) strategies used in educating their children include (1) through behavioral examples, early education, through refraction, through example. The contribution of research results can be used as enrichment material both theoretically and practically regarding family-based character education.